Using Google Workspace for Education to Improve Understanding of Differentiated Learning - Siti Nur Hidayati (Edumaspul: Jurnal Pendidikan, 2024)
The research entitled "Using Google Workspace for Education to Improve Understanding of Differentiated Learning" is based on the weakness of Islamic Religious Education teachers in understanding differentiated learning. The aim of this research is to critically analyze the use of Google Workspace for Education to understand differentiated learning for training participants consisting of Islamic Religious Education teachers. This research is classified as qualitative research. This research method was descriptive-analytical by collecting data in the form of literature from relevant research results, then analyzing and comparing it with the results of observations by researchers through training for teachers on differentiated learning using Google Workspace for Education. The research results showed, firstly, differentiated learning which consists of content/material differentiation, process differentiation, and product differentiation is very suitable to be delivered using the Google Workspace for Education platform which has various features; secondly, Google Workspace for Education has benefits as a method or medium for Trainers in training. Apart from that, Google Workspace for Education is also useful for teachers in teaching differentiated learning because the available elements suit various characteristics and tendencies of students; lastly, the use of Google Workspace for Education, supported by the use of the Canva and Padlet platforms, has an impact on increasing the training participants' good understanding of differentiated learning.